Recommended primary outcomes for clinical trials evaluating hemostatic blood products and agents in patients with bleeding: Proceedings of a National Heart Lung and Blood Institute and US Department of Defense Consensus Conference. Issue 2 (August 2021) - Spinella, Philip C.; El Kassar, Nahed; Cap, Andrew P.; Kindzelski, Andrei L.; Almond, Christopher S.; Barkun, Alan; Gernsheimer, Terry B.; Goldstein, Joshua N.; Holcomb, John B.; Iorio, Alfonso; Jensen, Dennis M.; Key, Nigel S.; et al.
Abstract : ABSTRACT: High-quality evidence guiding optimal transfusion and other supportive therapies to reduce bleeding is needed to improve outcomes for patients with either severe bleeding or hemostatic disorders that are associated with poor outcomes. Alongside challenges in performing high-quality clinical trials in patient populations who are at risk of bleeding or who are actively bleeding, the interpretation of research evaluating hemostatic agents has been limited by inconsistency in the choice of primary trial outcomes. This lack of standardization of primary endpoints or outcomes decreases the ability of clinicians to assess the validity of endpoints and compare research results across studies, impairs meta-analytic efforts, and, ultimately, delays the translation of research results into clinical practice. To address this challenge, an international panel of experts was convened by the National Heart Lung and Blood Institute and the US Department of Defense on September 23 and 24, 2019, to develop expert opinion, consensus-based recommendations for primary clinical trial outcomes for pivotal trials in pediatric and adult patients with six categories in various clinical settings. This publication documents the conference proceedings from the workshop funded by the National Heart Lung and Blood Institute and the US Department of Defense that consolidated expert opinion regarding clinically meaningful outcomes across a wide range of disciplines to provide guidance for outcomes of future trials of hemostatic products and agents for patients with active bleeding. Abstract : Supplemental digital content is available in the text.